The Translation of Madurese Proverb into Indonesian and English - Nur Ilham Alamsyah; Masduki Masduki (Journal of Social, Culture, and Language, 2024)
This study aims to analyze the translation of madurese proverbs in the book "Parebasan Madura" by Agus Tino (2008). The problem being examined is, what types of proverbs are being translated, what are the strategy used to translate the proverbs, and whether there is a shift in meaning in the translation results. The methodology used is qualitative analysis with a descriptive approach. The theory used in analyzing data sources is the theory of translation by Peter Newmark (1988). The data was obtained from the book and analyzed using close reading and content analysis techniques. The results of the study indicate that there are three types of proverbs found, namely aphorisms (16%), parables (8%), and idioms (76%). There are two strategies used to translate proverbs, namely literal translation and translation of proverbs into non-proverbs, and the writer found that there was a shift in meaning in some of the translation results. In conclusion, three types of proverbs were found in this study, where the most dominant type was idiom. There are two strategies used to translate these proverbs, and there is a shift in meaning in some of the translation results. Keywords: proverb, Madurese, theory of translation , Newmark, aphorisms, parables, idioms